Impact of Photoperiod on the Carbon Metabolic Pathways of Chlorella Vulgaris for Biomass Production and Nutrient Removal in Treating Nutrient-Rich Wastewater - Saman, N.A.M. (Springer Science and Business Media B.V., 2021)
Cultivation of Chlorella vulgaris has been done in different photoperiod to study the effect of photoperiod cycles on the on the carbon metabolic pathways of the microalgae species in order to enhance its biomass and lipid productions. Autotrophic, heterotrophic and three different photoperiod cycles of mixotrophic growth mode were evaluated for its biomass growth, carbon and nutrient uptakes and lipid yield. The studied photoperiods for mixotrophic growth are 16:8, 12:12 and 8:16Â h (light:dark hours). Heterotrophic condition produced much lower microalgal biomass and lipid yield compared to microalgae grown under autotrophic and mixotrophic condition. There is no significant difference in microalgal biomass yields observed under continuous illumination between 16:8Â h, 12:12Â h and 8:16Â h photoperiods. All studied parameters showed a near complete removal of COD on the second day of cultivation. Higher nitrogen removal was observed at longer photoperiod conditions. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.